TANBIH AS-SAHIB ALA AHKAM AL-MAKASIB AND ITS RELEVANCE TO THE ECONOMIC DEVELOPMENT IN NIGERIA - Bala Abu Bakar Muhammad (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
Islam views life as complete package, economic aspect being an important part of it. The most sensible area of economic system in Islam is rule of earning and expenditure. It was reported by Abu-Hurairah (R.A) that the prophet (SAW) said: “A time will come when people would not bother for their earning; it is Halal or Haram” (Bukhari: vol. 2, No .2056). The book titled Tanbih as-Sahib ala Ahkam al-Makasib (Alerting the Brother for the rules of Earning) by late Sultan Muhammad Bello through much light on the Islamic rules of earning and expenditure. The present paper analyzed the relevance of this important book to the areas of earning, expenditure and economic development, from the Islamic perspective. The author’s historical and educational background, as noted under the brief history of the author, points to the author’s ability to address economic issues in general earning and expenditure in particular. Islam memandang hidup sebagai paket yang lengkap, aspek ekonomi menjadi bagian penting darinya. Bidang sistem ekonomi yang paling masuk akal dalam Islam adalah aturan pendapatan dan pengeluaran yang makalah ini menyoroti dari Tanbih As-Sahib Ala Ahkam Al-Makasib. Karya ini mencoba menyoroti ajaran dasar Tanbih as-Sahib ala Ahkam al-Makasib (Memperingatkan Saudara tentang Aturan Penghasilan) oleh mendiang Sultan Muhammad Bello melalui banyak penjelasan tentang aturan Islam tentang penghasilan dan pengeluaran. Makalah ini menganalisis relevansi buku penting ini dengan bidang pendapatan, pengeluaran dan pembangunan ekonomi, dari perspektif Islam. Makalah ini juga menjelaskan kehidupan dan waktu penulis, dengan demikian menunjukkan kemampuan penulis untuk mengatasi masalah ekonomi dalam pendapatan dan pengeluaran umum pada khususnya dan relevansinya dengan Nigeria modern. Untuk mendapatkan data untuk makalah ini, desk review diadopsi sebagai metodologi pengumpulan data untuk penelitian ini.